Suitability of buttermilk for fermentation with Lactobacillus helveticus and production of a functional peptide-enriched powder by spray-drying - Burns, Patricia Graciela (2010)
Aim: To ferment buttermilk, a low-cost by-product of the manufacture of butter, with a proteolytic strain of Lactobacillus helveticus, to enhance its value by the production of a functional peptide-enriched powder. Methods and Results: Buttermilk was fermented with Lact. helveticus 209, a strain chosen for its high proteolytic activity. To enhance the release of peptidic fractions, during fermentation pH was kept at 6 by using NaOH, Ca(CO)3 or Ca(OH)2. Cell-free supernatant was recovered by centrifugation, supplemented or not with maltodextrin and spray-dried. The profile of peptidic fractions released was studied by RP-HPLC. The lactose, Na and Ca content was also determined. The powder obtained was administered to BALB ⁄ c mice for 5 or 7 consecutive days, resulting in the proliferation of IgA-producing cells in the small intestine mucosa of the animals. Conclusions: Buttermilk is a suitable substrate for the fermentation with Lact. helveticus 209 and the release of peptide fractions able to be spray-dried and to modulate the gut mucosa in vivo. Significance and Impact of the Study: A powder enriched with peptides released from buttermilk proteins, with potential applications as a functional food additive, was obtained by spray-drying. A novel use of buttermilk as sub- strate for lactic fermentation is reported.